Znanstveno raziskovanje in pedagoška dejavnost Fakultete za varnostne vede Univerze v Mariboru (1973–2023) (University of Maribor Press, 2023)
In 2023, the Faculty of Criminal Justice and Security, University of Maribor, Slovenia is celebrating its 50th anniversary. Eleven contributions present the development of the faculty in the scientific, research and pedagogical fields. Scientific Research and Pedagogical Activities at the Faculty of Criminal Justice and Security, University of Maribor (1973–2023). Contributions to the development of research, research projects, doctoral studies, and the development of research staff, on educational programs, individual areas of development in the field of police activity, security sciences, criminology, information security, criminology, law and general social science topics form a comprehensive picture of the development of the Faculty of Security Sciences and its predecessors in the last fifty years and present the reader a reflection on the development of the faculty in the future. In addition to the contributions of authors from the Faculty of Criminal Justice and Security, we also published reviews by prominent scholars in the fields of social science, criminology, and forensic psychology on their views on the development of criminal justice and security studies since 1973.